Scantly Known Grizzled Giant Squirrel (Ratufa macroura) of India: Status and Conservation - Paulraj, S.; Kasinathan, N. (Indian Forester, 1993)
The past and the present status and distribution of the scantly known Grizzled Giant Squirrel (Ratufa maeroura) are studied. The reasons for the decline of their population, the existing conservation problems and recommendations to improve their survival chances are discussed.